Availability of adequately iodised salt at household level and its associated factors in Robe town, Bale Zone, South East Ethiopia: community-based cross-sectional study - Nagasa Dida; Abiyot Legese; Abdurhim Aman; Bilkisa Muhamed; Teshome Damise; Tizita Birhanu; Sintayehu Hailu; Jiregna Darega; Bedasa Woldamichael; Eshetu Gadisa (The South African Journal of Clinical Nutrition, 2020)
Background: Iodine is a micronutrient required by the body in small amounts to prevent iodine deficiency disorder (IDD), which is a global public health concern. There were no specific data at household level of adequately iodised salt in the study area. Thus this study aimed to assess availability of adequately iodised salt and its associated factors at household level in Bale-Robe, South East Ethiopia. Methods: A community-based cross-sectional study was conducted in Robe town, Bale Zone, South East Ethiopia in April 2015. Data were collected through interviewer-administered questionnaires from a total of 367 households, which were identified through systematic random sampling. Salt iodine content was estimated using rapid testing kits at the household level. Descriptive statistics was used to determine the prevalence, and association between dependent and independent variables was computed by using bivariate and multivariable logistic regression. A p-value of < 0.05 was used to determine statistical significance. Results: Of 374 samples, 370 respondents were interviewed yielding a response rate of 99%. One-third (32.7%) of the household levels used adequately iodised salt. Respondents’ educational status, exposure to information on how to handle iodised salt and type of salt used by the respondents were independent factors for availability of adequately iodised salt at the household level. Salt that had been stored in a dry place was twice as likely to have an adequate iodine content compared with salt stored in a high-moisture area or near a fire (AOR = 2.13, CI = 1.19–3.72). Conclusion: Availability of adequately iodised salt at the household level was very low. Factors that were associated with household levels’ access to adequately iodised salt included educational level, age of the respondents and place where salt is stored, and had an effect on whether households iodise salt adequately. Strategies to educate residents regarding the appropriate storage conditions to minimise iodine losses in iodised salt are required in Bale-Robe district of South East Ethiopia.